III. Influence of the grip in the capacity of the rowing exercises in determining action potential levels for the deltoid and the pectoralis major muscle - Ferreira, M. I.; Büll, M. L. [UNESP]; Vitti, M. (My University, 1996)
The electromyographic activity of the shoulder muscles Deltoid-anterior portion (DA) and Pectoralis major-clavicular portion (PMC) was tested on 24 male volunteers using a 2 channel TECA TE4 electromyograph and Hewlett Packard surface electrodes during the execution of three different modalities of rowing exercises comparing middle grip with close grip. Statistical comparison showed that in both PMC and DA closed grip determined muscular solicitation higher than middlegrip excepting sitting rowing. The authors present some suggestions to the use of the tested exercises.